139 GHz UV phase-locked Raman laser system for thermometry and sideband cooling of 9Be+ ions in a Penning trap. (15th November 2021) - Mielke, J; Pick, J; Coenders, J A; Meiners, T; Niemann, M; Cornejo, J M; Ulmer, S; Ospelkaus, C
Abstract: We demonstrate the phase locking of two ultraviolet (UV) laser sources by modulating a fundamental infrared (IR) laser with fourth-order sidebands using an electro-optic modulator and the phase locking of one sideband to a second fundamental IR laser. Subsequent sum frequency generation and second harmonic generation successfully translates the frequency offset to the UV domain. The phase lock at 139 GHz is confirmed through stimulated Raman transitions for the thermometry of 9 Be + ions confined in a cryogenic Penning trap. This technique might be used for the sideband cooling of single 9 Be + ions as well as sympathetic cooling schemes and quantum-logic-based measurements in Penning traps in the future.